2016
DOI: 10.1186/s12913-016-1693-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health literacy, patient-centered communication and shared decision-making on patients’ satisfaction with care received in German primary care practices

Abstract: BackgroundFindings on the association between health literacy skills and patient-reported outcomes such as satisfaction with health care delivery are scarce. We explored the extent to which subjective health literacy skills and the perception of the application of patient-centered communication and shared decision-making are associated with patient’s satisfaction with care received by their general practitioner (GP).MethodsA nationwide cross sectional survey was administered in a random sample of 1125 German a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 39 publications
6
77
0
2
Order By: Relevance
“…Our results further suggest that eHealth literacy, trust in the health care system, and family self‐efficacy are important factors that contribute to satisfactory patient communication for patients with MM. These findings are in line with previous studies on effective patient‐physician relationships: Patient communication is significantly associated with eHealth literacy, trust in the health care system, and partner involvement . Also, our findings agree with what prior research has found that eHealth literacy is significantly associated with trust in health care systems .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results further suggest that eHealth literacy, trust in the health care system, and family self‐efficacy are important factors that contribute to satisfactory patient communication for patients with MM. These findings are in line with previous studies on effective patient‐physician relationships: Patient communication is significantly associated with eHealth literacy, trust in the health care system, and partner involvement . Also, our findings agree with what prior research has found that eHealth literacy is significantly associated with trust in health care systems .…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in line with previous studies on effective patientphysician relationships: Patient communication is significantly associated with eHealth literacy, trust in the health care system, and partner involvement. [20][21][22] Also, our findings agree with what prior research has found that eHealth literacy is significantly associated with trust in health care systems. 18,23,24 However, to the best of our knowledge, Our study had following strengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review by Berkman and colleagues to determine whether low health literacy is related to the poorer use of healthcare, outcomes, costs, and disparities in health outcomes among persons of all ages found that low literacy was associated with poorer health outcomes and the poorer use of healthcare services [19]. Association between good level of health literacy and treatment outcomes, patient satisfaction, and better quality of care was also found in recent studies [20,21].…”
Section: Patient Literacymentioning
confidence: 79%
“…Patients, providers, and health purchasers recognize that there is a role for decision and communication aides in orthopedic practice . Shared decision‐making can improve patients’ satisfaction with the care they receive .…”
Section: Discussionmentioning
confidence: 99%